Tinjauan Kebijakan Akuntansi Akun Khusus Belanja Penanganan Pandemi Covid-19: Studi Kasus Pada Kanwil DJPb Provinsi Lampung 2019-2021 - Rika Ayu Anjani; Imam Subroto (Polytechnic of State Finance STAN, 2022)
The Covid-19 pandemic causes a multiplier effect in some sectors including the accounting and financial sectors, influencing the government for making adjustments to the conditions. In the sector of state financial accountability, the government initiated the emergence of a new account in the form of a Special Account for handling the Covid-19 pandemic. The Covid-19 Special Account arises to allocate spending about Covid-19 which is issued through the Director General of Treasury Letter Number S-369/PB/2020. This study aims to review accounting and reporting policies for the emergence of new accounts related to Covid-19 at the Regional DJPb Office of Lampung Province. The method used in this research is a qualitative method (library study) accompanied by observation (interviews). The author in this case presents a Logic Model regarding the emergence of Special Accounts related to Covid-19 to facilitate reader understanding. Along with the research, the authors found differences in the disclosure of special accounts in the Notes to Financial Statements (CaLK). The results of this study are that the Regional DJPb Office of Lampung Province has implemented accounting and reporting policies in accordance with applicable regulations, namely PMK 225/PMK.05/2019 which was amended by PMK 234/PMK.05/2020. Keywords: Accounting Policy, Covid-19 Pandemic, Special Account